Competition of IL-1 and IL-1ra determines lymphocyte response to delayed stimulation with PHA. - Dabrowski, M P (2001)
BACKGROUND: Human peripheral blood mononuclear cells (PBMC) left in microcultures for 24h without mitogen do not respond to subsequent stimulation with PHA. They regain reactivity if the native culture medium is absorbed with other party lymphocytes or partially replaced with the medium from a PHA-stimulated culture. The observations suggest that, during the incubation, some inhibitory agent had accumulated in the culture medium. AIM: The study was performed to determine the nature of the observed phenomenon in respect of the possible role of monocytes and their products IL-1 and IL-1 receptor antagonist (IL-1ra), and to test for immunodiagnostic purposes the significance of quantifying the lymphocyte response to delayed stimulation with PHA in patients suffering from inflammatory prosesses. METHODS: Lymphocyte response to delayed stimulation with PHA, calculated as the lymphocyte-monokine interaction (LM) index, was determined in the microcultures of PBMC isolated from the blood of healthy donors or of patients with acute tonsilitis. The values of LM indices were compared with the ratios of IL-1ra/IL-1beta concentration estimated by enzyme-linked immunosorbent assay method in the culture supernatants. The influences of exogenous IL-1beta, IL-1ra, anti-IL1ra antibodies and antibiotic cefaclor on the monokine concentrations and on the values of LM index were tested. RESULTS AND CONCLUSIONS: The results show that the level of lymphocyte response to delayed stimulation with PHA (LM index) is inversely proportional to the ratio of IL-1ra/IL-1beta concentration in the culture. The low LM values at high IL-1ra/IL-1beta ratios in PBMC cultures from healthy donors, reversed proportions found in patients' PBMC (acute tonsilitis), and the cefaclor-induced reduction of LM value with correlated increase of the IL-1ra/IL-1beta ratio suggest that the LM assay may prove to be useful for immunodiagnostic purposes.